ANTIBACTERIAL ACTIVITY OF SOME FOLKLORE MEDICINAL PLANTS FROM SOUTH INDIA - Goud, M. Jaya Prakash; Komraiah, A.; Rao, K. Narasimha; Ragan, A.; Raju, V. S.; Charya, M. A. Singara (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
Antibacterial activity and phytochemical tests of eight whole plant methanol extracts belonging to family Euphorbiaceae were evaluated. In agar well diffusion assay the diameter of inhibition zones ranged from 3-13 mm. Phyllanthus emblica showed maximum activity of 13 mm. The MIC and MBC observed were 30-140 mcg/ml and 40-160 mcg/ml, respectively. P. piscatorum and P. emblica showed the lowest MIC (30 mcg/ml), P. emblica the lowest MBC (40 mcg/ml) and thus an effective inhibitor of the tested bacteria. Alkaloids, saponins and tannins were detected in 7 out of 8 tested plants.